Methods in Quaternary Ecology #10.Other Fossils - Warner, Barry (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1989)
Summary There are several plant and animal fossil types that are commonly encountered during routine analysis of other more conventional fossil groups. These less familiar ordiagnostic remains can be important paleo-ecological indicators, often complementing paleoenvironmental reconstructions basedon other more widely used fossil groups. The composition of the fossil sediment or peatit self contains important paleoecologicalinformation, in addition to the fossils contained within its matrix. Analysis of peat components can refine species identifications and, in general, yield useful information on peat-forming plant communities.